Answer: Below
Step-by-step explanation:
Just mutiply x on both sides which gives you 2x^2 + 12x then you mutiply 2x^2 then subtract that number on both sides and it gives you x = something then you distribute it on 8(something) - 18 you subtract
What exactly are you asking?
Answer:
Step-by-step explanation:
(9x-1)^-1/2 - (x+2)(9x-1)^-1/2
= (9x-1)^-1/2( 1 - (x + 2))
= (9x-1)^-1/2(-1 - x)
= -(x + 1)(9x-1)^-1/2
= -(x + 1) / (9x-1)^1/2
Answer:
YOUR ANWSER IS C
Step-by-step explanation:
HOPE THIS HELPED
I’d think it’s equated to the one, why I think that? Idek.